2018
DOI: 10.1016/s2214-109x(17)30448-5
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of clinical severity classification of new WHO childhood pneumonia guidance: a multi-hospital, retrospective, cohort study

Abstract: SummaryBackgroundManagement of pneumonia in many low-income and middle-income countries is based on WHO guidelines that classify children according to clinical signs that define thresholds of risk. We aimed to establish whether some children categorised as eligible for outpatient treatment might have a risk of death warranting their treatment in hospital.MethodsWe did a retrospective cohort study of children aged 2–59 months admitted to one of 14 hospitals in Kenya with pneumonia between March 1, 2014, and Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 41 publications
7
76
2
1
Order By: Relevance
“…Patient presented after 7 days of symptoms of pneumonia also had more radiologically proven pneumonia compare to patient presented earlier, because as duration of disease increases change in lung parenchyma would be more reflected in x-ray films. 12,13 In present study also patient stayed more than 7 days in hospital having clinically as well as radiologically severe pneumonia as observed in other studies. 14 Right side lung involved more than left side because right bronchus is wider and shorter than left bronchus and chance of aspiration and invasion of bacteria is more in right lung compare to left lung and similar findings found radiologically.…”
Section: Discussionsupporting
confidence: 82%
“…Patient presented after 7 days of symptoms of pneumonia also had more radiologically proven pneumonia compare to patient presented earlier, because as duration of disease increases change in lung parenchyma would be more reflected in x-ray films. 12,13 In present study also patient stayed more than 7 days in hospital having clinically as well as radiologically severe pneumonia as observed in other studies. 14 Right side lung involved more than left side because right bronchus is wider and shorter than left bronchus and chance of aspiration and invasion of bacteria is more in right lung compare to left lung and similar findings found radiologically.…”
Section: Discussionsupporting
confidence: 82%
“…We performed a separate analysis to explore the effect of nutritional status defined by weight-for-age z scores (WAZ) on clinical outcome (online supplementary material model 3 ). WAZ scores are often used to describe nutritional status in studies of children under 5 years,17 18 and these variables (weight and age) are well recorded in our data. We calculated WAZ scores using WHO child growth standards,19 excluding children over 10 years where there are no reference standards (WAZ scores are not reliable in the context of pubertal growth spurts) 19.…”
Section: Methodsmentioning
confidence: 60%
“…The pre-2018 Malawi IMCI protocol identified 2-fold more (10/13 = 77%) of the HC patients who died within 7 days of outpatient diagnosis than the 2014 WHO IMCI protocol (5/13 = 38%). These data and recent data from hospitalised children in Kenya showed that in routine care settings, presence of chest indrawing may require referral in some high-mortality settings [ 30 ]. Because not much is known about other factors that influenced adverse outcomes in these children with chest indrawing, such as care seeking and appropriate and timely treatment, further research is required to examine the beneficial effects of hospitalisation of children with chest indrawing in routine settings.…”
Section: Discussionmentioning
confidence: 85%